Anodic titania photonic crystals with high reflectance within photonic band gap via pore shape engineering. (15th March 2020) - Sadykov, A.I.; Kushnir, S.E.; Sapoletova, N.A.; Ivanov, V.K.; Napolskii, K.S.
Abstract: Anodizing of valve metals under oscillating conditions is one of versatile and reproducible methods of the preparation of one-dimensional photonic crystals. Here, an effect of anodizing voltage profile on morphology and optical properties of anodic titanium oxide photonic crystals is investigated. Samples are obtained by cyclic anodizing of titanium in ethylene glycol based electrolyte using sine, triangle, and square wave voltage versus charge density modulation. The optimization of anodizing parameters allowed us to prepare anodic titanium oxide photonic crystals with reflectance within the photonic band gap of up to 85%. Graphical abstract: Image, graphical abstract